Relative analysis between monetary policy variables and exchange rate fluctuations in Syria (2011-2022) models using comprehensive multiple self-reference trends (SVAR): Relative analysis between monetary policy variables and exchange rate fluctuations in Syria (2011-2022) models using comprehensive multiple self-reference trends (SVAR) (Journal of Hama University, 2025)
This study aims to analyze the relationship between monetary policy variables and exchange rate fluctuations in Syria, using a multiple linear regression model. It relied on financial data and reports published by the Central Bureau of Statistics in Syria, and publications of the Central Bank of Syria with monthly data, and then statistical analysis was conducted. For this data during the period (2011-2022) using the statistical program (EVIEWS12).The results of the study showed the existence of a statistically significant causal relationship between monetary policy variables and the exchange rate, and the presence of a statistically significant impact of monetary policy variables on exchange rate fluctuations. It was also shown that the occurrence of a positive structural change in the interest rate leads to a relatively weak response in the exchange rate. A positive structural change in (the growth rate of the real money supply M2r, inflation, GDP) produces effects of relatively varying intensity and duration of impact.
Keywords: Monetary policy, exchange rate, structural multiple autoregressive vector models (SVAR).